2014
DOI: 10.1016/j.ydbio.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Auto and cross regulatory elements control Onecut expression in the ascidian nervous system

Abstract: The expression pattern of Onecut genes in the central and peripheral nervous systems is highly conserved in invertebrates and vertebrates but the regulatory networks in which they are involved are still largely unknown. The presence of three gene copies in vertebrates has revealed the functional roles of the Onecut genes in liver, pancreas and some populations of motor neurons. Urochordates have only one Onecut gene and are the closest living relatives of vertebrates and thus represent a good model system to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The cell lineage of the photoreceptors in Ciona thus requires clarification. Specification of the ocellus‐associated photoreceptor lineages involves a Neurogenin ‐to‐ Onecut ‐to‐ Rx genetic cascade with Rx then activating Arrestin and Opsin1 gene expression . Nodal expression on the left side of the larvae represses Rx gene expression (and thus Arrestin and Opsin1 ), restricting photoreceptor cell formation to only the right side (Figure (b)).…”
Section: Step‐by‐step Cell Fate Specification In the Cnsmentioning
confidence: 99%
“…The cell lineage of the photoreceptors in Ciona thus requires clarification. Specification of the ocellus‐associated photoreceptor lineages involves a Neurogenin ‐to‐ Onecut ‐to‐ Rx genetic cascade with Rx then activating Arrestin and Opsin1 gene expression . Nodal expression on the left side of the larvae represses Rx gene expression (and thus Arrestin and Opsin1 ), restricting photoreceptor cell formation to only the right side (Figure (b)).…”
Section: Step‐by‐step Cell Fate Specification In the Cnsmentioning
confidence: 99%
“…Experiments were performed in triplicate, comparing at least 100 embryos for each single electroporated construct as described in Pezzotti et al . ().…”
Section: Methodsmentioning
confidence: 99%
“…LacZ staining of transgenic embryos was observed by histochemical detection of bgalactosidase activity. Experiments were performed in triplicate, comparing at least 100 embryos for each single electroporated construct as described in Pezzotti et al (2014).…”
Section: Transgenesismentioning
confidence: 99%
“…As further step in this regulatory cascade, we recently demonstrated that the Neurogenin transcription factor is involved in the direct HNF6/OC1 activation in photoreceptor cells (Pezzotti et al, 2014). An autoregulatory loop has also been evidenced, as responsible for the maintenance of HNF6/OC1 expression in these territories (Pezzotti et al, 2014). It would be interesting to investigate if these regulatory mechanisms, that control the expression of the C. intestinalis OC gene in photoreceptor territories, are also conserved in vertebrates.…”
Section: Ascidian Photoreceptor Genesmentioning
confidence: 99%